Descriptive analysis of thrust technique in synchronized swimming - Saju, J.; Chen Meng, M.; Wilson, B. D. (ISN-Bulletin, 2008)
Thrust is one of the elements of skillful exercise in synchronized swimming. The execution of underwater movements and corrections of the techniques are real problems faced by the coaches training synchronized swimmers. The Malaysian national synchronized swimmers were assessed and found to be deficient in the thrust technique performing a series of errors while executing movements underwater. A descriptive model for execution of the thrust technique in synchronized swimming was first developed. The exemplar technique was then executed by the synchronized swimming coach and the underwater movements were video recorded with the help of underwater video using Peeper-Scope and analyzed using SiliconCOACH PRO 6.1.5. Feed- back guidelines were then given to the synchronized swimmers to describe the correct sequence of underwater movements to be performed in order to improve aesthetic appraisal above water.